Trauma-related symptoms and severity among women in the Pacific Rim. Issue 1 (2nd January 2019) - Reeves, Elizabeth; Bernal de Pheils, Pilar; Silva, Susan G.; Jaramillo, Diva; Uribe, Tulia; Tiwari, Agnes; Canaval, Gladys Eugenia; Mendoza Flores, Maria Eugenia; Belknap, Ruth Ann; Humphreys, Janice C.
Abstract: Current understandings of the effects trauma exposure on women's health are limited because prior research has largely focused on intimate partner and sexual violence in homogenous samples. In this descriptive study, the authors examined the relationships between lifetime trauma exposure and psychological well-being among women across the Pacific Rim. Psychological well-being differed significantly between the four locations and increased trauma exposures were related to poorer psychological well-being across and within locations. The authors report relevant findings on the relationship between trauma exposure and psychological well-being and provide evidence for future research to enhance knowledge on the effects of trauma in women's lives.